Culture Management through the balanced scorecard : a case study - Woodley, P. M. (Cranfield University, 2007)
Neuro Linguistic Programming argues that repeating previous behaviour will only succeed in delivering previous outcomes. Kaplan and Norton’s Balanced Scorecard is about getting different results. For successful change, managing complex and higher functions such as managing motivation and the beliefs of staff members must take their place alongside environmental and capability issues such as physical equipments. Mechanistic processes such as the Balanced Scorecard can nevertheless be used to manage softer aspects of change such as culture, as part of an integrated holistic management system. This needs to be done through adoption of key Balanced Scorecard processes. A principal feature of the Balanced Scorecard which can be applied here is the development of a cause-and-effect model of cultural issues with clear and measurable linkages to organisational performance. The degree to which national or organisation culture supports or conflicts with these processes needs to be considered. However, the Balanced Scorecard must be implemented properly in order to be effective in managing the organisation. This research examines the Balanced Scorecard implementation in one organisation and examines the inter-relationship with associated cultural issues. Criteria are defined for managing and assessing Balanced Scorecard implementations. From the main case study a model for understanding the importance of organisational culture is developed. A cultural measurement tool is then developed and tested within this organisation to show how the cultural measurement can be integrated into the Balanced Scorecard regime. Effective measurement is an essential precursor to effective culture management. The results of cultural measurement are used to explore potential management issues. The strands of work are merged in a final set of case studies that use the developed models to assess Balanced Scorecard implementations in other organisations. These case studies illustrate how cultural issues have affected Balanced Scorecard development.